Current and projected demand for nurses working in general practice in Ireland - Connolly, Sheelah; Flanagan, Ellen (ESRI, 2024)
General practice is an integral part of the Irish healthcare system. Demand for general practice services is expected to increase in the coming years due to both (i) a growing and ageing population, and ii) policy proposals seeking to re-orientate healthcare delivery towards the community setting. Consequently, there is a need to increase the general practice workforce to deliver on this projected increase in demand. The number of GP training places have increased in the last number of years; however an increase in the number of nurses working in general practice could also help address growing demands on the sector. The aim of the research in this report is: To examine the current utilisation of practice nurse services in Ireland. To make projections about the future demand for practice nurse services. To identify challenges and potential facilitators to increasing the number of nurses working in general practice in Ireland.